THE INFLUENCE OF SHARIA ECONOMIC SHADOW AND INFORMATION INEQUALITY ON PROFIT-SHARING MSME FINANCING DECISIONS - Yesi Safitri; Dhea Alpina Giawa; Wahdinil Jannah; Siti Mukti Intan (Universitas Efarina, 2023)
This study aims to analyze the influence of the Islamic shadow economy and information asymmetry on the profit-sharing financing decisions of micro and small enterprises (MSMEs). The method used is multiple regression analysis based on data collected from respondents involved in MSME financing. The results show that simultaneously, the variables of the Islamic shadow economy and information asymmetry have a significant influence on MSME financing decisions, with a significance value of 0.002. However, partially, only information asymmetry has a significant effect, while the Islamic shadow economy does not show a significant influence. The coefficient of determination (R²) of 14.9% indicates that other factors outside the model also affect MSME financing decisions. This research provides insight into the importance of accurate information management in MSME financing and highlights that the Islamic shadow economy does not have a direct significant influence in this context.